Synergistic interactions in multispecies biofilm combinations of bacterial isolates recovered from diverse food processing industries - Sadiq, Faizan Ahmed; De Reu, Koen; Burmølle, Mette; Maes, Sharon; Heyndrickx, Marc (Frontiers in Microbiology, 2023)
Most biofilms within the food industry are formed by multiple bacterial species which co-exist on surfaces as a result of interspecies interactions. These ecological interactions often make these communities tolerant against antimicrobials. Our previous work led to the identification of a large number (327) of highly diverse bacterial species on food contact surfaces of the dairy, meat, and egg industries after routine cleaning and disinfection (C&D) regimes. In the current study, biofilm-forming ability of 92 bacterial strains belonging to 26 genera and 42 species was assessed and synergistic interactions in biofilm formation were investigated by coculturing species in all possible four-species combinations. Out of the total 455 four-species biofilm combinations, greater biofilm mass production, compared to the sum of biofilm masses of individual species in monoculture, was observed in 34 combinations. Around half of the combinations showed synergy in biofilm mass > 1.5-fold and most of the combinations belonged to dairy strains. The highest synergy (3.13-fold) was shown by a combination of dairy strains comprising Stenotrophomonas rhizophila, Bacillus licheniformis, Microbacterium lacticum, and Calidifontibacter indicus. The observed synergy in mixed biofilms turned out to be strain-specific rather than species-dependent. All biofilm combinations showing remarkable synergy appeared to have certain common species in all combinations which shows there are keystone industry-specific bacterial species which stimulate synergy or antagonism and this may have implication for biofilm control in the concerned food industries.